Analysis on Performance of HTS DC Cables with Counter-Flow Cooling Mode - Cheng, Jian; Luo, Zhiyi; Zhang, Fengyin; Zhao, Weili; Zhang, Quan; Wang, Bangzhu; Meng, Ziqing (Journal of Electronics and Electrical Engineering, 2025)
With the increase in power demand, the transmission distance of the High-Temperature Superconducting (HTS) Direct Current (DC) cable is required to be longer. However, the impact of temperature changes caused by the increase in cable length on cable performance is rarely considered. This paper focuses on the effects of two different cooling arrangements on the performance of km-class HTS DC cables. The analysis reveals that the cooling method significantly influences the temperature distribution along the cable, which in turn affects the critical current and effectiveness of the cable. The findings underscore the importance of optimizing cooling strategies to enhance the reliability and efficiency of km-class HTS DC cables with ripple current in practical applications.